+0  
 
0
100
1
avatar+128 

Let a, b, c be the roots of the cubic polynomial x^3 - x - 1 = 0. Find a(b - c)^2 + b(c - a)^2 + c(a - b)^2.

 

thank you!

 Apr 2, 2021
 #1
avatar+121004 
+1

We   can write  the  polynomial  as

 

x^3  +  0x^2  -  1x  -  1

 

Sum of  the roots   =    0

So       a  + b  +  c   =   0   implies  that

a + b   = - c

a + c   - b

b +  c  =    -a

 

Product of  the  roots  =  1

So

abc  = 1

 

 

 

a(b - c)2^2   =  ab^2 - 2abc  + ac^2

b(c - a)^2    =  bc^2 - 2abc + ba^2

c(a - b)^2  =    ca^2  - 2abc  + cb^2

 

Sum of  this  can  be  written as   =   ab ( a  + b)  +  ac ( a + c)  + bc ( b + c)  -  6abc     

 

Substituting  we  have

 

ab (-c)   + ac ( - b)  +  bc ( -a)   -  6abc        =

 

- abc  -  abc   - abc   - 6abc   =

 

-9 (abc)  = 

 

-9 (1)   =

 

-9

 

cool cool cool      

 Apr 2, 2021

15 Online Users

avatar
avatar